Facilitation of the development of a one-data application service business process documentation for the Buton Selatan District Communication and Informatics Office - Eko Satria; Anwar Sadat; Andy Arya Maulana Wijaya; La Ode Muhammad Azhar Sya’ban; Harry Fajar Maulana; Abdul Rahim; Jundi Syahrul Ramadhan (Universitas Muhammadiyah Magelang, 2024)
Business process is intended to support the success of the One Data policy, which is mandated in Presidential Regulation Number 39 of 2019 concerning One Indonesia Data. The problem is that the Communication and Information Office of South Buton Regency does not yet have a business process map for the One Data Application service. The purpose of this community service is to improve organizational administration, specifically targeting the One Data Service in South Buton Regency. The objective of this business process map is to provide a comprehensive overview of the implementation of programs and activities at the Communication and Information Office of South Buton Regency. The implementation method in this community service activity is through a focus group discussion (FGD). This activity has produced a business process map for the Communication and Information Office of South Buton Regency to support the provision of effective, efficient, integrated, and accountable data services.